Acute effects of surgery on emotion and personality of brain tumor patients: surgery impact, histological aspects, and recovery - Campanella, Fabio (Neuro Oncol, 2015)
BACKGROUND: Cognitive effects of brain surgery for the removal of intracranial tumors are still under investigation. For many basic sensory/motor or language-based functions, focal, albeit transient, cognitive deficits have been reported low-grade gliomas (LGGs); however, the effects of surgery on higher-level cognitive functions are still largely unknown. It has recently been shown that, following brain tumors, damage to different brain regions causes a variety of deficits at different levels in the perception and interpretation of emotions and intentions. However, the effects of different tumor histologies and, more importantly, the effects of surgery on these functions have not been examined. METHODS: The performance of 66 patients affected by high-grade glioma (HGG), LGG, and meningioma on 4 tasks tapping different levels of perception and interpretations of emotion and intentions was assessed before, immediately after, and (for LGG patients) 4 months following surgery. RESULTS: Results showed that HGG patients were generally already impaired in the more perceptual tasks before surgery and did not show surgery effects. Conversely, LGG patients, who were unimpaired before surgery, showed a significant deficit in perceptual tasks immediately after surgery that was recovered within few months. Meningioma patients were substantially unimpaired in all tasks. CONCLUSIONS: These results show that surgery can be relatively safe for LGG patients with regard to the higher-level, more complex cognitive functions and can provide further useful information to the neurosurgeon and improve communication with both the patient and the relatives about possible changes that can occur immediately after surgery.